Vaksinator Vaksin Booster Covid-19 di Desa Metuk Mojosongo Boyolali - Sutanta Sutanta (Samodra Ilmu: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2023)
The third dose vaccination program is held as a continuation of the primary vaccination. In addition, this booster vaccine is also an effort to restore decreased immunity and clinical protection in the population found based on the results of the sero survey. The implementation of the Covid-19 booster vaccine aims to accelerate the recovery of the immune system of all levels of society, especially in the village of Metuk Mojosongo. STIKes Estu Utomo as an educational institution implementing the Tri Darma of Higher Education dedicates nursing lecturers as co-19 booster vaccine vaccinators. This community service was carried out on Wednesday, July 13, 2021 at 09.00 – 1.00 WIB at the Metuk Mojosongo Boyolali village hall. This activity was attended by 250 participants, namely 177 women (71%) and 73 men (9%). Activities are coordinated by the head of the service team with the assistance of village officials and midwives. The activities in community service are in the form of a co-19 booster vaccine vaccinator. After being given a booster vaccination, 250 community members attended according to the plavon prepared by the Health Service. All participants underwent vaccination well, none of them experienced difficulties or disturbance from the participants.